Adverse events supposedly attributed to COVID-19 vaccines in patients treated by Pulmonology outpatient service in hospitals of the Essalud-Piura network, 2022 - Farfán-Chávez, Luis Gabriel (2026)
Introduction: COVID-19 vaccines have been essential in controlling the pandemic, but concerns have arisen regarding their adverse effects. This study evaluates the incidence of adverse effects in vaccinated patients attending Pneumology outpatient clinics in the EsSalud Piura network in 2022. Methods: A cross-sectional study was conducted with 254 patients over 18 years of age who received at least one dose of a COVID-19 vaccine (Pfizer, Sinopharm, or AstraZeneca). Data were obtained through a review of medical records and structured interviews. Adverse effects were classified as local or systemic. Crude (RPc) and adjusted prevalence ratios (RPa) were calculated using Poisson models, adjusting for age, sex, comorbidities, and prior COVID-19 infection. Results: Most patients 60.6% were ≤60 years old, and 86.2% had comorbidities. RPa showed that respiratory infection sequelae significantly increased the risk of adverse effects after the third dose (RPa: 1.66; 95% CI: 1.17-2.35; p=0.004). Additionally, patients over 60 years and females were also associated with a higher likelihood of adverse effects (RPa: 1.29; 95% CI: 0.92-1.80 and RPa: 1.15; 95% CI: 0.83-1.60, respectively). Conclusion: COVID-19 vaccines, particularly the third dose, showed a higher incidence of adverse effects in patients with respiratory sequelae. Women and those over 60 years also had a higher risk of adverse effects.